Modulating M1/M2 macrophage polarization with plant metabolites: a therapeutic strategy for rheumatoid arthritis - Yang, Yuanyuan; Wang, Xiaoyu; Kong, Youqian; Pan, Yang; Yang, Xiadong; Zhang, Ziyi; Li, Zeguang (Frontiers in Pharmacology, 2025)
Rheumatoid arthritis (RA) is a systemic autoimmune disorder marked by persistent synovitis and the degradation of joint cartilage and surrounding bone due to inflammation. A variety of immune cells, particularly macrophages, are involved in the initiation and maintenance of inflammation in RA, along with leukocyte adhesion and migration, matrix breakdown, and neovascularization. Environmental and internal stimuli drive macrophages to polarize into two major phenotypes: M1, which exerts strong bactericidal effects and contributes to chronic inflammation and tissue injury, and M2, which inhibits inflammation and facilitates tissue repair. The dysregulation of M1/M2 macrophage polarization is a key contributor to the pathogenesis and disease progression of RA. Plant metabolites are typically characterized by multi-component, multi-target, and multi-pathway actions, and their underlying mechanisms may include regulation of immune function, especially the balance of macrophage polarization. Current evidence indicates that such metabolites may provide certain therapeutic benefits and a relatively manageable safety profile in the management of RA and related disorders. In this review, we summarize the potential mechanisms by which various plant metabolites modulate macrophage function and polarization under inflammatory conditions, providing evidence for their clinical application in RA treatment and offering new insights into precision therapy for RA.